Argumentation Based on Logic Programming - García, Alejandro Javier (2018)
Among of the programming paradigms based on formal logic, Logic Programming has been a successful effort to create a declarative model of expressing computational processes producing significant theoretical and practical results; as such, the area has contributed computationally attractive systems with remarkable success in many applications. By blending concepts from the areas of Logic Programming and Argumentation, Defeasible Logic Programming (DeLP) proposes a computational reasoning system with an argumentation engine at its core capable of obtaining answers from a knowledge base which is represented with a language that uses logic programming constructs extended with defeasible rules. The careful integration of foundational intuitions and concepts from both areas has formulated a framework that inherits from the logic programming field its expressivity and computational efficiency and receives from argumentation theory a human-like reasoning model facilitating its use in applications. In this chapter, the basic elements of logic programming will be succinctly recalled, and the DeLP language will be formally introduced together with the warranting process that obtains the answers for queries. DeLP-Servers, which give possibly distributed client agents running on remote hosts the ability to consult different reasoning services are presented. Finally, some extensions and applications of DeLP are briefly described.